Multi-Actor Collaborative Village Tourism Governance Policy in Strengthening Community Resilience by the Tanjungsari Village Government, Ciamis Regency, Indonesia - Regi Refian Garis; Irfan Nursetiawan; Muhammad Younus (Government & Resilience, 2026)
Village tourism development serves as a strategic instrument for fostering local economic growth, promoting equitable welfare, and ensuring environmental sustainability. This study examines the implementation of a multi-actor collaborative governance model in village tourism development by the Tanjungsari Village Government, Ciamis Regency, and identifies key factors influencing its effectiveness within a sustainable development framework. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis, involving stakeholders such as village officials, Tourism Awareness Groups (Pokdarwis in Indonesian), and local communities. The analysis applies the Edward III policy implementation model, focusing on communication, resources, disposition, and bureaucratic structure. Findings reveal that while collaborative governance has been initiated, several challenges persist, including limited human resource capacity, suboptimal policy communication, insufficient integration of digitalization into formal governance frameworks, and an underdeveloped bureaucratic system. Importantly, this study underscores that strengthening community resilience emerges as a critical dimension, as adaptive capacity, local participation, and social cohesion significantly influence the sustainability of tourism initiatives. The novelty lies in the proposed Policy Practice Integration Model, which emphasizes dynamic alignment between formal policies and community-based practices, positioning village institutions and Pokdarwis as hybrid actors and digitalization as an adaptive instrument to enhance resilient and sustainable village tourism governance.